Immunomodulatory and antitumour effects of abnormal Savda Munziq on S180 tumour-bearing mice - Aikemu Ainiwaer; Umar Anwar; Yusup Abdiryim; Upur Halmurat; Berké Bénédicte; Bégaud Bernard; Moore Nicholas (BMC, 2012)
Abstract Background Abnormal Savda Munziq (ASMq), a traditional uyghur medicine, has shown anti-tumour properties in vitro. This study attempts to confirm these effects in vivo and measure effects on the immune system. Methods Kunming mice transplanted with Sarcoma 180 cells were treated with ASMq (2-8 g/kg/day) by intra-gastric administration compared to model and cyclophosphamide (20 mg/kg/day). After the 14th day post tumour implant, thymus, liver, spleen and tumours were removed, weighed, and processed for histopathological analysis. Blood samples were also taken for haematological and biochemical analyses including TNF-α , IL-1 β and IL-2. Splenic lymphocyte function was measured with MTT; lymphocyte subpopulations were measured by flow cytometry. Results ASMq treated animals had reduced tumour volume compared to model and increased concentrations of TNF-α, IL-1β and IL-2 compared to untreated and to cyclophosphamide-treated animals. No histopathological alterations were observed. The absence of viable S180 cells and the presence of necrotic cells and granulation tissue were observed in tumour tissue of treated animals. The effect on T lymphocytes was unclear. Conclusions ASMq confirmed in vivo anti-tumour effects observed in vitro, which may be at least in part mediated by increased immune activity.